2011
DOI: 10.1007/s11897-011-0064-6
|View full text |Cite
|
Sign up to set email alerts
|

Beta-3 Adrenoceptors as New Therapeutic Targets for Cardiovascular Pathologies

Abstract: Catecholamines play a key role in the regulation of cardiovascular function, classically through ß(1/2)-adrenoreceptors (AR) activation. After ß(3)-AR cloning in the late 1980s, convincing evidence for ß(3)-AR expression and function in cardiovascular tissues recently initiated a reexamination of their involvement in the pathophysiology of cardiovascular diseases. Their upregulation in diseased cardiovascular tissues and resistance to desensitization suggest they may be attractive therapeutic targets. They may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 49 publications
0
37
0
1
Order By: Relevance
“…The observed blood pressure changes in individuals tend to cancel themselves out in the whole population but the discrepancy between preclinical and clinical physiological findings remains unexplained [10,12]. We recognize that single measurements of blood pressure may not be entirely representative for the individual and 24-h blood pressure [12,13]. Nonetheless, clinical trials have shown that mirabegron increases the heart rate in healthy volunteers [14], as well as in patients with overactive bladder [11].…”
Section: Commentmentioning
confidence: 98%
See 1 more Smart Citation
“…The observed blood pressure changes in individuals tend to cancel themselves out in the whole population but the discrepancy between preclinical and clinical physiological findings remains unexplained [10,12]. We recognize that single measurements of blood pressure may not be entirely representative for the individual and 24-h blood pressure [12,13]. Nonetheless, clinical trials have shown that mirabegron increases the heart rate in healthy volunteers [14], as well as in patients with overactive bladder [11].…”
Section: Commentmentioning
confidence: 98%
“…Our findings are nonetheless reassuring given the many, and often serious, cooccurring cardiovascular diseases among our patients and do not suggest that heart rate increments pose a major clinical problem in a non-selected treatment group. Cardiovascular safety studies of mirabegron have not demonstrated any direct effects of mirabegron on the sinus node [13], no negative inotropic effects [15], and no QT interval prolongation or ventricular arrhythmias [14]. In randomized comparisons between mirabegron and antimuscarinic drugs no consistent ECG differences were observed [16].…”
Section: Commentmentioning
confidence: 99%
“…Recently, a study showed preliminary encouraging data using a β3 agonist, BRL37344, in mice submitted to transaortic constriction 56 although the specificity of this molecule as an agonist for the murine β3-AR is somewhat disputed. 57 Sorrentino et al 58 have recently demonstrated in a postinfarction murine model that nebivolol, a β2-AR, and likely β1-AR biased agonist, 59 which was previously shown to activate β3-AR in the human ventricle, 60 improves LV function and survival early after myocardial infarction likely beyond the effects provided by conventional β1-receptor blockade. 58 The Study of the Effects of Nebivolol Intervention on Outcomes and Rehospitalisations in Seniors with Heart Failure (SENIORS) trial demonstrated the effect of nebivolol on all-cause mortality or cardiovascular hospitalization in elderly patients with HF.…”
Section: 29mentioning
confidence: 99%
“…In normal heart, b 3 -ARs may mediate a moderate negative inotropic effect, but in heart failure it may protect against adverse effects of excessive catecholamine stimulation by action on excitation--contraction coupling, electrophysiology, or remodeling. No evidence suggests direct action of b 3 -ARs agonists on the sinus node and, therefore, modifications in HR [82]. However, a study conducted in healthy volunteers demonstrated that mirabegron increased the HR in a dose-dependent manner [67].…”
Section: Expert Opinionmentioning
confidence: 99%